A blend containing docosahexaenoic acid, arachidonic acid, vitamin B12, vitamin B9, iron and sphingomyelin promotes myelination in an in vitro model. (1st December 2020) - Hauser, Jonas; Sultan, Sébastien; Rytz, Andreas; Steiner, Pascal; Schneider, Nora
ABSTRACT: During the development of the central nervous system, oligodendrocytes (OLs) are responsible for myelination, the formation of the myelin sheath around axons. This process enhances neuronal connectivity and supports the maturation of emerging cognitive functions. In humans, recent evidence suggests that early life nutrition may affect myelination. In the present study, we investigated the impact of a blend containing docosahexaenoic acid, arachidonic acid, vitamin B12, vitamin B9, iron and sphingomyelin, or each of these nutrients individually, on oligodendrocyte precursor cells (OPCs) proliferation and maturation into OLs as well as their myelinating properties. By using an in vitro model, developed to study each step of myelination, we found that the nutrient blend increased the number of OPCs and promoted their differentiation and maturation into OLs, as measured by quantifying A2B5 positive cells, myelin-associated glycoprotein (MAG) positive cells and area, myelin binding protein (MBP) positive cells and area, respectively. Moreover, measuring myelination by quantifying the overlapping signal between neurofilament and either MAG or MBP revealed a positive effect of the blend on OLs myelinating properties. In contrast, treatment with each individual nutrient resulted in differential effects on the various readouts. This work suggests that dietary intake of these nutrients during early life, might be beneficial for myelination.